Immunological indexes for assessing parameters of cardiovascular system in athletes of different qualification - M. A. Myagkova; Z. V. Bobrova; S. N. Petrochenko (Медицинская иммунология, 2023)
Timely diagnosis and prevention of cardiovascular diseases is based on markers that detect changes in the athlete’s body at an early stage of disease. To implement this task, it is important to use novel laboratory techniques. We have carried out a comparative determination of immunological markers, specific antibodies to angiotensin, bradykinin, histamine, dopamine, serotonin and functional indicators of the cardiovascular system in athletes of various qualifications. The object of study included athletes of the Russian national teams who underwent an in-depth examination (IME) as part of medical survey. The participants were divided into groups depending on the sport arts and qualifications. Representatives of the group “Cyclic sports” included athletes without a category of 30 people and 29 qualified athletes (1st step, Candidate Master, Master of Sports, etc.). The “Combat sports” group consisted of 32 people without a category and 31 athletes with qualifications similar to those indicated above. Athletes of “Speed-strength” sports are represented by a group of 31 people without a category and 29 athletes with qualifications. The functional parameters of the cardiovascular system included analysis of heart rate, systolic blood pressure and diastolic blood pressure, which were compared with control values established for the athletes. The immunological indexes were determined in blood serum of the athletes and in subjects from control group by means of the solid-phase ELISA method using conjugated antigens of angiotensin, bradykinin, histamine, dopamine, serotonin for absorption on the plates. To compare the indexes, a control group of 30 people without cardiovascular symptoms was examined. Diastolic blood pressure for athletes of cyclic sports and combat sports was below the control values, and, for athletes of speed-strength sports, it was higher than in control group. A decrease in diastolic blood pressure for the above subgroup of athletes may indicate characteristic adaptive physiological changes in myocardium. The levels of immune-related indexes for serotonin, dopamine for the athletes of all groups corresponded to the control values. The only exception concerned qualified athletes of cyclic sports, which significantly differed from the normal values, compared to athletes without a sports category. Significantly high immunological parameters for histamine and angiotensin did not depend on the athlete’s qualification. In athletes involved in speed-strength sports, the levels of indexes for bradykinin did not differ from the normal values, and, for athletes in cyclic sports and combat sports, they significantly exceeded the norm.We have shown that different levels and types of sports activities affect the performance of cardiovascular system in their own way. The changes in immunological parameters reflect regulatory state of cardiovascular system. Accordingly, their simultaneous increase against the control may indicate participation in the development of cardiovascular diseases. The differences in their levels for athletes involved in combat sports, cyclic and speed-strength sporting activities show deeper changes in regulatory systems associated with duration and level of physical activities.